2022
DOI: 10.1097/01.aoa.0000853588.45095.88
|View full text |Cite
|
Sign up to set email alerts
|

Experience of 300 Cases of Prenatal Fetoscopic Open Spina Bifida Repair: Report of the International Fetoscopic Neural Tube Defect Repair Consortium

Abstract: (Am J Obstet Gynecol. 2021;225:678.e1–678.e11. [Epub June 3, 2021]) Prenatal repair of open spina bifida (OSB) showed increased chance of independent ambulation and increased outcomes of ventriculoperitoneal shunting compared with postnatal repair in a multicenter randomized controlled trial in the Management of Myelomeningocele Study (MOMS). The technique, involving a hysterotomy, has risks regarding the uterine incision used. Due to the risks, fetal surgeons worldwide have been attempting to repair… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 2 publications
0
8
0
Order By: Relevance
“…Prenatal SBA repair has become widely adopted in the last decade after the positive outcome of the MOMS trial 14,33 . While a number of surgical techniques have been adopted and results are difficult to compare, it is believed that watertightness of fetal SBA layered repair is critical for good neurological outcome 39–41 . In this study, we have demonstrated in a validated lamb model that watertight layered fetal SBA repair is neuroprotective, as evidenced by 100% reversal of hindbrain herniation, low CSF leakage at the repair site, better hindlimb motor function, higher neuronal density in the hippocampus and corpus callosum and a larger area of reactive astrocytes at the lesion epicenter compared with in unrepaired lambs.…”
Section: Discussionmentioning
confidence: 99%
“…Prenatal SBA repair has become widely adopted in the last decade after the positive outcome of the MOMS trial 14,33 . While a number of surgical techniques have been adopted and results are difficult to compare, it is believed that watertightness of fetal SBA layered repair is critical for good neurological outcome 39–41 . In this study, we have demonstrated in a validated lamb model that watertight layered fetal SBA repair is neuroprotective, as evidenced by 100% reversal of hindbrain herniation, low CSF leakage at the repair site, better hindlimb motor function, higher neuronal density in the hippocampus and corpus callosum and a larger area of reactive astrocytes at the lesion epicenter compared with in unrepaired lambs.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, fetoscopic approaches reported higher rates of placental abruption, preterm premature rupture of membranes, and premature birth [26][27][28] compared to open techniques [8,[29][30][31][32]. Interestingly, vaginal birth rates after fetoscopic fetal SB repair differed from 0% [26,27] up to 30-60% [28,[33][34][35]. Regarding subsequent pregnancies after fetoscopic SB repair, Sanz Cortes et al [36] reported 10 subsequent pregnancies in a cohort of 73 women.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with the published results of percutaneous surgery, laparotomy-assisted fetoscopic repair [10, 18] appears to be associated with longer interval between surgery and delivery, lower PROM rate, and higher vaginal delivery rate, with a higher mean gestational age at delivery [12, 19]. An international registry of 300 children reported similar perinatal and neurosurgical outcomes in the first 12 months of life of children undergoing prenatal fetoscopic SBA repair compared to open surgery [20]. A recent publication reporting 16 cases describes similar outcomes to the ones we report hereby [21].…”
Section: Discussionmentioning
confidence: 99%